Poly[[diaqua(μ(2)-4,4′-dipyridyl sulfide-κ(2) N:N′)(4,4′-dipyridyl sulfide-κN)(2-hydroxy-5-sulfonatobenzoato-κO (1))nickel(II)] dihydrate] - Du, Zhong-Xiang (International Union of Crystallography, 2008)
The asymmetric unit of the title helical coordination polymer, {[Ni(C(7)H(4)O(6)S)(C(10)H(8)N(2)S)(2)(H(2)O)(2)]·2H(2)O}(n), is comprised of an Ni(II) ion, one 5-sulfosalicylic acid dianion (HSSA), two 4,4′-dipyridylsulfide (4,4′-dps) ligands, and two coordinated and two uncoordinated water molecules. The Ni(II) ion is coordinated by two water molecules, one carboxylate O atom of the HSSA dianion and three N atoms from three 4,4′-dps ligands in a distorted octahedral environment. Half of the 4,4′-dps ligands are μ(2)-bridging ligands which link adjacent Ni(II) centers, forming a one-dimensional helical structure along the b axis. This helical structure is further stabilized by O—H⋯O intra- and intermolecular hydrogen bonds.